Cardiorespiratory responses to stationary running at different cadences in water and on land - Alberton, C. L.; Tartaruga, M. P.; Pinto, S. S.; Cadore, E. L.; da Silva, E. M.; Kruel, L. F. M. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The aim of the current study was to analyze the heart rate (HR), oxygen uptake (VO2), and percentage of maximal HR (%HRmax) and VO2 (%VO2max) responses to stationary running exercise performed at different cadences on land (LA) and in water (WA). Methods. The sample comprised 12 apparently healthy women (mean age 22.33±0.57 years). The exercise was performed in WA and LA environments (interval of 2 hours) at submaximal cadences of 60, 80 and 100 bpm for a period of 4 min at each cadence (interval of 5 min). HR and V.O2 data were collected using a Polar S610TM and Aerosport KB1-C gas analyzer, respectively. The data were analyzed using factorial ANOVA for mixed models, Tukey`s post hoc and Pearson`s correlation test, with P<0.05 (SPSS version 13.0). Results. Significant differences were found between the environments for all variables (HR, VO2, %HRmax and %VO2max: P<0.001), with higher values for LA. Significant differences were found between the cadences for all variables (HR, VO2, %HRmax and %V.O2max: P<0.001). The effect of the interaction environment*cadence was only significant for %HRmax (P=0.041). The correlations between HR and VO2 (WA: r=0.857; P<0.001 and LA: r=0.556; P<0.001) and %HRmax and %VO2 (WA: r=0.860; P<0.001 and LA: r=0.798; P<0.001) exhibited high and significant correlation coefficient values, especially for WA, suggesting that variable increased linearly with increases in cadence. Conclusion. The results suggest that cardiorespiratory responses to stationary running exercise are lower in WA, though they can be maximized by increasing the execution cadence.